Joint effect of airflow limitation and emphysema on postoperative outcomes in early-stage nonsmall cell lung cancer. Issue 6 (3rd November 2016) - Shin, Sumin; Park, Hye Yun; Kim, Hyunkyung; Kim, Hong Kwan; Choi, Yong Soo; Kim, Jhingook; Um, Sang-Won; Chung, Myung Jin; Kim, Hojoong; Kwon, O Jung; Zo, Jae Ill; Guallar, Eliseo; et al.
This study aims to evaluate the joint effect of severity of airflow limitation and emphysema on postoperative pulmonary complications (PPCs) and overall survival after complete resection in patients with early-stage nonsmall cell lung cancer (NSCLC). We retrospectively studied 413 male patients with pathologic stage I or II NSCLC between 2007 and 2009. Severity of airflow limitation was defined based on forced expiratory volume in 1 s. Emphysema was defined by ≥5% low attenuation area at −950 HU. In multivariable-adjusted analyses, the adjusted odds ratio (aOR) for any PPC, comparing patients with moderate-to-severe airflow limitation to those without airflow limitation, was 2.23, and the aOR comparing patients with emphysema to those without emphysema was 1.77. However, the joint effect of airflow limitation and emphysema was much higher than expected from the independent effects of both factors (aOR 8.90). Moreover, patients with coexisting moderate-to-severe airflow limitation and emphysema had significantly poorer overall survival than any other group. Patients with moderate-to-severe airflow limitation and emphysema had almost nine times the risk of PPCs and poorer survival than patients with neither of these conditions. Integrated assessment of airflow limitation severity and emphysema is necessary for the optimal selection of candidates for lung resection surgery of early-stage NSCLC. Postoperative outcomes after complete resection in early-stage NSCLC depends on both airflow limitation and emphysema http://ow.ly/fAjl3049YKn